Serum copper to zinc ratio: Relationship with aging and health status. (November 2015) - Malavolta, Marco; Piacenza, Francesco; Basso, Andrea; Giacconi, Robertina; Costarelli, Laura; Mocchegiani, Eugenio
Highlights: The serum Cu to Zn ratio is sensible to age related destabilizing events. High serum Cu to Zn ratio is associated with mortality in elderly. Nutrition, oxidative stress, inflammaging and hormones impact on Cu to Zn ratio. Serum Cu to Zn ratio modulates immune defense, growth stimuli and stress response. Cu to Zn changes with aging might reflect the attempt of the body to repair itself. Abstract: The serum concentrations of copper (Cu) and zinc (Zn) are strictly regulated by compensatory mechanisms that act to stabilize them within certain ranges of nutritional intake. However, there are mechanisms that are built to decrease serum concentration of Zn and to increase serum concentration of Cu in the presence of inflammatory conditions, so that a common feature of several age-related chronic diseases is an increase of the Cu to Zn ratio (CZr). Although the clinical potential of CZr has been extensively investigated, few authors addressed the mechanisms that mainly contribute to the increase of CZr in serum during aging, which signals drive this change and how cells respond to these changes. This review focuses on this topic and discusses how an increase of CZr during aging could reflect the homeostatic shade from a general systemic "growth and reproduction" status typical of juvenile age to a "repair and maintenance" status that evolved to preserve health status during old age.